Enhancing Learning Agility, Job Crafting, and Innovative Work Behavior: Strategies to Thrive in A Competitive Industry - Gisella, Verren; Zamralita, Zamralita; Purwono, R. Urip (International Journal of Social Service and Research, 2025)
The current industrial era is extremely fast-paced and dynamic. Companies require employees who can adapt quickly and enhance the company's competitiveness through innovative ideas. The aim of this study is to examine the role of Learning Agility as a predictor of Innovative Work Behavior, with Job Crafting as a mediator. Learning agility is the ability to quickly learn new skills and adapt to changing situations. Innovative Work Behavior involves identifying problems and implementing new ideas. Job crafting refers to how employees adjust their job demands and resources. This study was conducted with 158 employees, aged 18–58 years, with a minimum of one year of work experience. The measurement tools in this study were the Learning Agility Scale by Wardhani et al. (2022), the Innovative Work Behavior Scale by Jong & Den Hartog (2010), and the Job Crafting Scale by Tims et al. (2012). Data processing was carried out using IBM SPSS Statistics 30.0. The results of the study showed that Learning Agility has a significant influence on Innovative Work Behavior (p=.000; p< .05), Learning Agility has a significant influence on Job Crafting (p=.000; p<.05), Job Crafting has a significant influence on Innovative Work Behavior (p=.0426; p<.05), and Job Crafting partially mediates the relationship between Learning Agility and Innovative Work Behavior. The implications of this study suggest that managers and employees should develop Learning Agility capabilities and implement Job Crafting strategies to exhibit Innovative Work Behavior.